Explaining consumer perspectives on mobile news services: a study in South Africa - Maurya, Rubina (Department of Information Systems, 2019)
Access to news supports the development of democratic societies. News can promote sustainable community development and encourage healthy social, political, and economic engagement. Mobile news services (MNSs) are one means to reach out to citizens to share news and provide citizens with a forum to review and voice their opinion. However, the extant of research related to technology adoption of MNSs is limited. Therefore, the purpose of this study is to propose a framework which articulates factors influencing the adoption of MNSs particularly by the citizens of South Africa. A review of the literature on MNSs and technology adoption helped to identify potential factors that could influence adoption. This study considers existing theoretical evidence and provides new empirical evidence, to extend current theoretical understanding. Mixed methods research supported the identification of influencing factors and relationships which support the adoption of MNSs. The resultant MNS adoption model offers new insights into the personal and social factors, attributes of adopters and attributes of MNSs influencing adoption of MNSs. The model included influencing factors such as social concerns, psychological drivers, motivators, trust sensitivities for accessing information, relative advantage and value, observability, usability, portability, immediacy, compatibility, and facilitating conditions. The identified relationships between the individual factors introduced a new perspective to the prior models of technology adoption, by highlighting connections between the social environment, the adopter, and MNSs. A pragmatic approach and statistical analysis of the data validated the relationships, and the model. The decision to adopt was found to be directly affected by sixteen interlinked factors. The findings are important to mobile service providers, designers, and developers, in their endeavour to satisfy their consumer’s needs and desires.